Solutions of human resources for tourism development in Ninh Binh province in the new situation - Pham Cong Ngoc; Ho Thi Xuan Hong (Journal of Forestry Science and Technology, 2025)
This paper aims to analyze the current factors affecting human resources in different job positions in tourism sector in Ninh Binh province. It gives a thorough investigation into various factors affecting the quantity and quality of human resources currently as well as the future context of the tourism service industry in the province such as physical health, professional qualifications (including work experience, vocational skills and foreign language proficiency) as well as professional attitudes. By analyzing the statistical data, the paper results have indicated that, in order to enhance the local natural tourism potential and boost up the competence of the industry’s workforce to meet the increasing demands of domestic and overseas tourists, one of the most crucial factors that needs to be constantly improved is human resources with quality in both physical and capability. However, due to both subjective and objective factors, the quality of human resources of the province’s tourism industry is still ineffective, leading to several disadvantages on the development of local tourism. From these findings, a number of solutions and recommendations are proposed to elevate the perspectives of human resources, contributing to bringing the tourism industry of Ninh Binh province to higher level.